2014
DOI: 10.1002/etc.2512
|View full text |Cite
|
Sign up to set email alerts
|

Urban and agricultural pesticide inputs to a critical habitat for the threatened delta smelt (Hypomesus transpacificus)

Abstract: The Cache Slough complex is an area of tidal sloughs in the Sacramento-San Joaquin River Delta of California (USA), and is surrounding by irrigated agricultural lands. Among the species of concern in the area is the delta smelt (Hypomesus transpacificus), a federally listed threatened species. Releases of the organophosphate insecticide chlorpyrifos and pyrethroid insecticides were examined to determine whether they represented a threat to the copepods on which delta smelt feed (Eurytemora affinis and Pseudodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 31 publications
(54 reference statements)
4
35
1
Order By: Relevance
“…The SRDWSC moves urban runoff from West Sacramento to the eastern portion of Cache Slough, and Ulatis Creek, a major freshwater input, carries urban and agricultural runoff and secondary wastewater into western Cache Slough, just upstream of the Cache Slough sampling location in our study (Fig. 1; Weston et al 2014). Weston et al (2014) repeatedly detected acute toxicity to Hyalella azteca following storms in both western Cache Slough and Ulatis Creek, and attributed the toxicity largely to pyrethroids in urban runoff.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The SRDWSC moves urban runoff from West Sacramento to the eastern portion of Cache Slough, and Ulatis Creek, a major freshwater input, carries urban and agricultural runoff and secondary wastewater into western Cache Slough, just upstream of the Cache Slough sampling location in our study (Fig. 1; Weston et al 2014). Weston et al (2014) repeatedly detected acute toxicity to Hyalella azteca following storms in both western Cache Slough and Ulatis Creek, and attributed the toxicity largely to pyrethroids in urban runoff.…”
Section: Discussionmentioning
confidence: 81%
“…1; Weston et al 2014). Weston et al (2014) repeatedly detected acute toxicity to Hyalella azteca following storms in both western Cache Slough and Ulatis Creek, and attributed the toxicity largely to pyrethroids in urban runoff. In a two-year study, Werner et al (2000) found that of the 24 sites sampled throughout the Delta, Ulatis Creek most frequently showed acute toxicity to Ceriodaphnia dubia (6 of 21 monthly samples were acutely toxic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, toxicity was found to be higher in agricultural areas (Weston et al 2008). Weston et al (2014) studied pesticides in Cache Slough and found no pyrethroids during the dry season, but pyrethroids were toxic to a test organism after storms. Urban and some agricultural runoff into Ulatis Creek, a tributary of Cache Slough, was responsible.…”
Section: First Flushmentioning
confidence: 99%
“…dilutus larvae and H. azteca are often used in toxicity testing because of their high sensitivity to pyrethroids and organophosphates (Ankley et al 1994b;Deanovic et al 2013;Rakotondravelo et al 2006b;Weston et al 2014). Both species are highly relevant for environmental risk assessments as they are found in water bodies throughout the Americas and are important food sources for fish, amphibians, aquatic insects, and other organisms.…”
Section: Introductionmentioning
confidence: 99%